2018
DOI: 10.1186/s40880-018-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and research opportunities for lung cancer screening in China

Abstract: Following publication of the results of the National Lung Screening Trial in the United States, a randomized controlled trial in Italy (ITALUNG) and two simulation studies in China reported similar findings in 2017 favoring lung cancer screening with low-dose computed tomography among smokers. With such advances in lung cancer screening, worldwide interest has gradually shifted from evaluating whether refining lung cancer screening protocols is effective in preventing deaths. However, there are several practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…A multidimensional model incorporating radiomics score and liquid biopsy for the prediction of malignant and benign pulmonary nodules advanced stages by diagnosis, resulting in a low 5-year overall survival rate (1,2), whereas patients with stage I lung cancer who undergo surgery have a 10-year survival rate of 92% (3). Therefore, the early screening and treatment of people at high risk for lung cancer can improve patient prognosis and reduce the risk of death from lung cancer (4,5). The benefits demonstrated in the National Lung Screening Trial have led to the widespread implementation of lung cancer screening worldwide (6).…”
Section: Original Articlementioning
confidence: 99%
“…A multidimensional model incorporating radiomics score and liquid biopsy for the prediction of malignant and benign pulmonary nodules advanced stages by diagnosis, resulting in a low 5-year overall survival rate (1,2), whereas patients with stage I lung cancer who undergo surgery have a 10-year survival rate of 92% (3). Therefore, the early screening and treatment of people at high risk for lung cancer can improve patient prognosis and reduce the risk of death from lung cancer (4,5). The benefits demonstrated in the National Lung Screening Trial have led to the widespread implementation of lung cancer screening worldwide (6).…”
Section: Original Articlementioning
confidence: 99%
“…1,2 The key to lowering lung cancer mortality is early detection and treatment. [3][4][5] However, because of the lack of typical symptoms of early lung cancer, patients frequently miss the best time for diagnosis and treatment. 6 Previous studies have reported that a low-dose computed tomography (CT) examination can detect early lung cancer and significantly reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer continues to be the leading cause of cancer‐related death worldwide 1,2 . The key to lowering lung cancer mortality is early detection and treatment 3–5 . However, because of the lack of typical symptoms of early lung cancer, patients frequently miss the best time for diagnosis and treatment 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Risk-based or personalized screening approaches are being studied to overcome these challenges [ 6 ]. We believe that a deeper understanding of the spectrum of risk factors for LC and applying technologies such as machine learning and knowledge graphs (KGs) will generate more cost-effective screening solutions.…”
Section: Introductionmentioning
confidence: 99%